The Aesthetic Appreciation of Nature: Essays on the Aesthetics of Nature - Budd, Malcolm (Oxford Clarendon, 2002)
The aesthetics of nature has over the last few decades become an intense focus of philosophical reflection, as it has been ever more widely recognised that it is not a mere appendage to the aesthetics of art. Everyone delights in the beauty of flowers, and some are thrilled by the immensity of mountains or of the night sky. But what is involved in serious aesthetic appreciation of the natural world? Malcolm Budd presents four interlinked studies in the aesthetics of nature, approaching the subject from a variety of angles. As well as developing Budd's own original ideas, the book provides a comprehensive treatment of Kant's classic aesthetics of nature, and an encyclopaedic critical survey of recent literature on the subject.
Keywords: Esthetics